Cognitive abilities of students in the use of biology laboratory equipment: a study case at SMAN 1 Rasau Jaya, Kubu Raya District - Alda, Alda; Candramila, Wolly; Mardiyyaningsih, Asriah Nurdini (Biosfer: Jurnal Pendidikan Biologi, 2025)
Laboratory activities enhance students’ understanding of scientific concepts through hands-on experience and develop their scientific thinking. Proficiency in using key instruments like microscopes, pipettes, Bunsen burners, and thermometers is crucial for safe and successful experiments. This study at SMAN 1 Rasau Jaya aimed to assess students’ understanding and proficiency in utilizing these six laboratory tools, with the goal of improving the quality of laboratory-based learning. The research employed a descriptive qualitative method to evaluate the cognitive abilities of 12th-grade students at SMA Negeri 1 Rasau Jaya in relation to the use of laboratory equipment, including microscopes, dropper pipettes, measuring cups, Bunsen burners, thermometers, and O’Haus balances. The sample consisted of a single study group with diverse student characteristics. Data were collected through a questionnaire consisting of yes/no questions designed to assess students’ knowledge of proper tool usage. The questionnaire was completed manually within a limited time frame for each question. The findings showed that students generally had good to fairly good knowledge of laboratory equipment. Tools like microscopes, dropper pipettes, and Bunsen burners were better understood, while measuring cups, thermometers, and O’Haus balances required further instruction. The study emphasizes the importance of practical experience and familiarity with tools in developing proficiency. The study highlights the significant role of familiarity and practical experience in developing tool-use proficiency. These findings underscore the importance of achieving a balance between theoretical instruction, understanding of tool mechanisms, and hands-on laboratory practice.